2019
DOI: 10.1016/j.ijpddr.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the utility of moxidectin for the control of parasitic nematodes in the face of developing anthelmintic resistance

Abstract: Macrocyclic lactone (ML) anthelmintics are the most important class of anthelmintics because of our high dependence on them for the control of nematode parasites and some ectoparasites in livestock, companion animals and in humans. However, resistance to MLs is of increasing concern. Resistance is commonplace throughout the world in nematode parasites of small ruminants and is of increasing concern in horses, cattle, dogs and other animals. It is suspected in Onchocerca volvulus in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 162 publications
(228 reference statements)
0
109
0
Order By: Relevance
“…A review of the reported efficacy data has shown moxidectin to be the most potent of the MLs in preventing the development of D. immitis in dogs [4]. Moxidectin generally has a longer elimination half-life and a larger volume of distribution than both ivermectin and milbemycin, which allow for a longer persistence and greater distribution of moxidectin in host tissues, including adipose tissue where it is active against migrating D. immitis larvae [6]. These attributes make moxidectin an attractive molecule to optimize in new heartworm preventative products in the face of emerging ML heartworm resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the reported efficacy data has shown moxidectin to be the most potent of the MLs in preventing the development of D. immitis in dogs [4]. Moxidectin generally has a longer elimination half-life and a larger volume of distribution than both ivermectin and milbemycin, which allow for a longer persistence and greater distribution of moxidectin in host tissues, including adipose tissue where it is active against migrating D. immitis larvae [6]. These attributes make moxidectin an attractive molecule to optimize in new heartworm preventative products in the face of emerging ML heartworm resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moxidectin is a ML that is available in heartworm preventative products worldwide with 100% efficacy reported against ML-susceptible D. immitis strains [4]. Moxidectin has unique attributes that make it an attractive molecule for use as a heartworm preventative in the face of emerging resistance [6]. Recent reports showed that increasing the oral monthly dosage of moxidectin and the number of consecutive monthly doses administered improved its efficacy against MLresistant D. immitis, and that 24 µg/kg was selected as the optimal dosage for further commercial development [4].…”
Section: Introductionmentioning
confidence: 99%
“…46 )). Moreover, the chemical structure of moxidectin with high lipophilicity increases the half-life of the drug 47 , an observation that may be linked to its higher drug efficiency, as compared to other anthelmintic agents. Ivermectin on the other hand has been safely used in immunocompromised patients to treat scabies 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…The potential of these agents to improve the response to steroids also in good responding cases and potentially to decrease toxicity could be tested in a clinical trial. In nematodes, anthelmintic agents target glutamategated chloride channels to increase intracellular chloride concentrations, which is lethal to the parasites 47 . Since these chloride channels are lacking in humans, anthelmintics must have alternative targets to activate cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Ivermectin(IVM) is a macrolide antiparasitic drug with a 16-membered ring derived from avermectin that is composed of 80% 22,23-dihydroavermectin-B1a and 20% 22,23-dihydroavermectin-B1b [ 1 ]. In addition to IVM, the current avermectin family members include selamectin, doramectin and moxidectin [ [2] , [3] , [4] , [5] ] ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%